2013
DOI: 10.4208/cicp.451011.260112s
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of Hydrodynamics for Multi-Relaxation Time Lattice Boltzmann using the Moment Approach

Abstract: A general analysis of the hydrodynamic limit of multi-relaxation time lattice Boltzmann models is presented. We examine multi-relaxation time BGK collision operators that are constructed similarly to those for the MRT case, however, without explicitly moving into a moment space representation. The corresponding 'moments' are derived as left eigenvectors of said collision operator in velocity space. Consequently we can, in a representation independent of the chosen base velocity set, generate the conservation e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…T ai f eq i = 0 if T a is a ghost eigenvector. This emphasizes the physical interpretation of the model, but is otherwise not necessary for a faithful implementation of hydrodynamics [43]. It is often convenient to imagine the f i to be the elements of vector in the space spanned by the velocity vectors c i .…”
Section: Discrete Velocity Boltzmann Equationmentioning
confidence: 99%
“…T ai f eq i = 0 if T a is a ghost eigenvector. This emphasizes the physical interpretation of the model, but is otherwise not necessary for a faithful implementation of hydrodynamics [43]. It is often convenient to imagine the f i to be the elements of vector in the space spanned by the velocity vectors c i .…”
Section: Discrete Velocity Boltzmann Equationmentioning
confidence: 99%
“…The eigenvectors of the collision matrix in these approaches differ from the current ones only by a factor and additions of conserved eigenvectors. Kaehler et al [24] showed that this ensures that the collision terms are equivalent. For the equilibrium distribution in moment space we obtain…”
Section: Lattice Boltzmann Methodsmentioning
confidence: 99%
“…This derivation follows the approach developed by Kaehler et al [24]. We write the lattice Boltzmann eqn.…”
Section: Hydrodynamic Limitmentioning
confidence: 99%
“…The correspondence between the LBE and the macroscopic behavior that it simulates can be shown through different approaches. The standard procedure is the Chapman-Enskog analysis, and one alternative is the recursive substitution developed by Wagner [25] and further developed by Holdych et al [26] and Kaehler and Wagner [27]. Up to second order terms, both procedures result in the same behavior, and it is not known if differences at higher orders will occur.…”
Section: A the Lattice Boltzmann Equationmentioning
confidence: 99%